The ingredients and microbiology studies of traditional eye medicine in a teaching hospital in Southwest Uganda - Lee, C. P.; Aggarwal, S.; Arunga, S.; Johnson, S. (The Journal of Ophthalmology of Eastern, Central and Southern Africa, 2020)
The aim of this study was to investigate the usage, ingredients, and microbiological profile of Traditional Eye Medicine (TEM) at a teaching hospital in southwest Uganda. Methods: This was a single-center prospective pilot study that included 11 individuals who used TEM before presenting to a tertiary eye center of the Mbarara University of Science and Technology (MUST) between February 15th, 2017, and February 24th, 2017. We noted the patients’ demographics, chief complaints, reasons for using TEM, and duration of treatment. We obtained the 19 samples of TEM and reviewed botanical contents and the microbiologic profile via gram staining, KOH staining, and cultures on blood-heart infusion agar, blood agar, chocolate agar, and potato dextrose agar. Results: The most common reason for using TEM was cultural belief, followed by the cost of western medications and distance to the eye clinic. Cataracts and allergic conjunctivitis were the most common diagnoses made. The major contents were botanical sources. Sixteen out of 19 samples (84%) showed positive microbial culture; 6 samples were polymicrobial, and 10 were monomicrobial. Klebsiella species was the most common microorganism, being isolated from 13 samples. Other bacterial organisms included Staphylococcus aureus and Bacillus species. Fungal species such as candida and aspergillus species were isolated as well. Conclusion: Most of our patients used TEM due to cultural beliefs. Eighty-five percent of the TEM samples showed positive microbiology culture, predominantly with Klebsiella species. Further microbiologic studies are warranted to identify the correlation between the use of TEM, corneal contamination, and corneal ulcers.
Keywords: Traditional Eye Medicine (TEM); Bacterial keratitis; Fungal keratitis